The Effect of Tax Avoidance, Liquidity, Profitability, on Capital Structure of Indonesia Stock Exchange’s Listed Companies - Putri, Ayu Nadia; Dwiarti, Rina (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to analyze the impact of tax avoidance, liquidity, and profitability on capital structure in diversified industrial subsector companies for the period 2021–2023. The population of the study includes all diversified industrial subsector companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sample was selected using purposive sampling, resulting in 24 companies that met the selection criteria. The analytical techniques used include classical assumption tests and multiple linear regression analysis. The study's results indicate that tax avoidance does not have a significant impact on capital structure. Liquidity, on the other hand, has a significant negative impact on capital structure, indicating that companies with higher liquidity levels tend to have lower capital structures. Profitability, like tax avoidance, does not significantly affect capital structure. However, tax avoidance, liquidity, and profitability together have a significant impact on capital structure. These findings highlight the importance of considering these factors in managing capital structure in diversified industrial subsector companies.